Development of a Diffraction-Based Micro-Diameter Measurement Instrument - Siti Muthoharoh; Supriyadi Supriyadi; Bambang Subali (Universitas Negeri Semarang, 2026)
This study presents the development and evaluation of a low-cost, non-contact micro-diameter measurement instrument based on Fraunhofer diffraction for physics education and basic laboratory use. The prototype integrates a 650 nm laser diode, a 16-channel photodiode array, and an ESP32 microcontroller to automate diffraction pattern acquisition and analysis. Repeated measurements were conducted on human hair and banana midrib fibers, with twenty trials for each sample, to examine measurement stability and precision. The system consistently captured diffraction patterns within expected physical ranges. The mean diameter of the human hair sample was 1.99 μm with a standard deviation of 0.12 μm and a coefficient of variation (CV) of 6.03%, indicating high precision. For banana midrib fibers, the mean diameter was 3.22 μm with a standard deviation of 0.37 μm and a CV of 11.49%, which is acceptable for heterogeneous biological materials. Narrow 95% confidence intervals for both samples confirm reliable mean estimation. The results demonstrate that the developed instrument provides stable, repeatable measurements while remaining affordable and simple to operate. This prototype is therefore suitable as an instructional laboratory tool for teaching diffraction concepts and quantitative measurement skills in physics education, as well as for basic research in resource-limited laboratory environments.